Rhinopithecus bieti (Primates: Cercopithecidae). (5th October 2018) - Harding, Lee E; Han, Lian-Xian
Abstract: Rhinopithecus bieti Milne-Edwards, 1897 is 1 of the largest and most northerly colobine monkeys. It lives at the highest recorded elevations for a nonhuman primate, 2, 625–4, 700 m. It has a restricted range between the Yangtze and Mekong Rivers in Yunnan and Xizang (Tibet) Provinces, mainland of China, in 15–20 groups comprising 6 isolated populations. It lives in multimale–multifemale bands of up to 480 individuals comprising cohesive 1-male units of < 20 individuals in nonoverlapping home ranges. Bands may have 1 or more all-male units. Mating and parturition are seasonal. With a total population of about 3, 500, it is 1 of the most endangered primates and is listed as "Endangered" by the International Union for Conservation of Nature and Natural Resources.